The great spectacle 250 years of the Royal Academy Summer Exhibition - Hallett, Mark 1965-; Turner, Sarah Victoria (Royal Academy of Arts, 2018)
The Royal Academy's Summer Exhibition is the world's longest running annual display of contemporary art, and one of its largest. Ever since 1769 the Academy's exhibition rooms have been crowded for some two months each year with thousands of paintings and sculptures by many of Britain's leading artists. These spectacular displays have provided artists with crucial competition, inspiration and publicity, and captured the interest of millions of visitors. 'The Great Spectacle' takes the reader on a fascinating journey to tell the story of these exhibitions. Many treasured works of British art were first shown on the walls of the RA: portraits by Reynolds and Gainsborough, the mighty landscapes of Turner and Constable, and the Pre-Raphaelites, who caused such a critical and cultural furore. The chapter on the twentieth century will reveal the RA's relationship with British modernism, right up to the 2018 Summer Exhibition, which will be coordinated by Grayson Perry CBE RA. Exhibition: Royal Academy of Arts, London, UK (12.06.-19.08.2018)
First published on the occasion of the exhibition "The great spectacle: 250 years of the Summer Exhibition", Royal Academy of Arts, London, 12 June-19 August 2018
Keywords: Royal Academy of Arts; Geschichte 1769-2018; Ausstellungskatalog -- Royal Academy of Arts -- 12.06.2018-19.08.2018 -- London